Pakistan : Use of Fund Resources-Request for Emergency Assistance-Staff Report; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Pakistan. (IMF Staff Country Reports; Country Report, 2010)
The floods in Pakistan are a natural disaster of massive proportions. The overall impact will critically depend on how the floods will affect agricultural output along the Indus and its tributaries. The Pakistani authorities request financial assistance under the IMF policy for Emergency Natural Disaster Assistance (ENDA). Based on these developments, prior to the floods, IMF staff had projected a GDP growth rate of 4u percent and an annual inflation rate of 11.5 percent for 2010/2011. The economic outlook has deteriorated sharply as a result of the floods.